Investigating Husband's Support and Murrotal Therapy Effects on Maternal Anxiety in Childbirth - Sri Wahyuni; Nin Suharti (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
First-time mothers may find childbirth difficult; they frequently feel intense anxiety, stress, and terror as the due date draws near, particularly in the third trimester of pregnancy when there is a higher chance of an early birth. The aim of the research was to ascertain the impact of Murottal therapy and husband support on the anxiety levels of expectant mothers during labor at Badrul Aini Mother and Child Hospital. This study uses a cross-sectional research approach and is quantitatively analytical. In August 2023, the study was carried out at the Badrul Ain Mother and Child Hospital. All of the pregnant patients in this study came to the Badrul Aini Mother and Child Hospital to give birth. The sampling technique was random, so the research sample was obtained from as many as 50 pregnant women. Data collection techniques in this study used questionnaires and observation techniques. Data analysis used correlation and multiple linear regression tests with SPSS software processing. The results showed that husband support (p-value = 0.006) and murrotal therapy significantly reduced the anxiety level of pregnant women (p-value = 0.001). However, the hypothesis that Murrotal therapy moderates the effect of husband support on anxiety levels was not supported. The importance of the husband's role in providing emotional and psychological support during labor and confirming the effectiveness of Murrotal therapy in managing maternal anxiety. Healthcare providers should consider involving husbands in prenatal care and labour, and Murrotal therapy can be a valuable tool in managing pregnant women's anxiety. Keywords: Childbirth, Husband's Support, Murrotal, Therapy, Pregnant mother's anxiety